Hypoxia: The “Invisible Pusher” of Gut Microbiota - Han, Ni; Pan, Zhiyuan; Liu, Guangwei; Yang, Ruifu; Yujing, Bi (Frontiers in Microbiology, 2021)
Oxygen is important to the human body. Cell survival and operations depend on oxygen. When the body becomes hypoxic, it affects the organs, tissues and cells and can cause irreversible damage. Hypoxia can occur under various conditions, including external environmental hypoxia and internal hypoxia. The gut microbiota plays different roles under hypoxic conditions, and its products and metabolites interact with susceptible tissues. This review was conducted to elucidate the complex relationship between hypoxia and the gut microbiota under different conditions. We describe the changes of intestinal microbiota under different hypoxic conditions: external environment and internal environment. For external environment, altitude was the mayor cause induced hypoxia. With the increase of altitude, hypoxia will become more serious, and meanwhile gut microbiota also changed obviously. Body internal environment also became hypoxia because of some diseases (such as cancer, neonatal necrotizing enterocolitis, even COVID-19). In addition to the disease itself, this hypoxia can also lead to changes of gut microbiota. The relationship between hypoxia and the gut microbiota are discussed under these conditions.